2008
DOI: 10.1677/joe-07-0627
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin secretion is more closely aligned to energy balance than with feeding behaviour in the grower pig

Abstract: Secretory characteristics of the ghrelin profile for the pig are still unknown. Our objective was to clarify the mechanisms that influence ghrelin secretion during differing feeding patterns. Pigs were initially fed a commercial pelleted diet offered ad libitum and blood samples collected for 24 h at intervals of 1 h. The pigs were then entrained for 17 days to a twice daily interval feeding regimen (0900-1000 and 1600-1700 h) and blood samples were collected for 12 h (0800-2000 h). This was followed by a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
3
19
0
Order By: Relevance
“…These results indicate that ghrelin secretion may be altered by season, and therefore could play a role in the seasonal changes in food intake seen in hibernators. Scrimgeour et al (2008) provide evidence that ghrelin may reflect long term energy balance, acting as a feedback signal to the hypothalamus to defend an optimum body mass by controlling food intake. If a hibernator’s energy stores are depleted to a sufficiently low level during torpor, it will arouse and attempt to eat to make up the difference (Mrosovsky et al, 1970).…”
Section: Discussionmentioning
confidence: 92%
“…These results indicate that ghrelin secretion may be altered by season, and therefore could play a role in the seasonal changes in food intake seen in hibernators. Scrimgeour et al (2008) provide evidence that ghrelin may reflect long term energy balance, acting as a feedback signal to the hypothalamus to defend an optimum body mass by controlling food intake. If a hibernator’s energy stores are depleted to a sufficiently low level during torpor, it will arouse and attempt to eat to make up the difference (Mrosovsky et al, 1970).…”
Section: Discussionmentioning
confidence: 92%
“…The potential interaction between insulin and ghrelin concentrations in serum is a subject of debate (Soares and Leite-Moreira, 2008). In pigs, Govoni et al (2005) found a negative correlation between insulin and acylated ghrelin concentrations, whereas Scrimgeour et al (2008) were unable to detect any correlation. In the present study, the diets that triggered a greater insulin response in the early postprandial period also resulted in a greater concentration of acylated ghrelin in the late postprandial phase, which might be related to the inhibitory effects of insulin on ghrelin production (Erdmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, total ghrehn (acylated -|-des-acylated) concentration in serum may be indicative of chronic changes in energy status. Scrimgeour et al (2008) reported that total ghrelin increased with feed restriction as compared with free access to feed. Acylated ghrehn, however, was more responsive to the nutrient content of the diet and was less affected by the feeding regimen (Owusu-Asiedu et ai., 2006;Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, some reports demonstrate that ghrelin does not play a primary role in initiating feeding nor as a regulator of feeding patterns [21]. Indeed, accumulating data suggests that ghrelin's role may be directed to maintain overall energy homeostasis as observed in humans [22, 23] and in pigs [24]. …”
Section: Introductionmentioning
confidence: 99%